Breastfeeding and complementary feeding practices and management of wasting of the young children: The significance and the updates - Februhartanty, Judhiastuty (World Nutrition Journal, 2024)
Human milk is the standard for infant nutrition and growth. World Breastfeeding Week (WBW) is essential in raising awareness, providing support, and advocating for breastfeeding, which leads to healthier communities. Over recent decades, there has been a significant increase in breastfeeding rates, a broader acknowledgment of human milk as the primary food for infants, and a deeper understanding of breastfeeding's role in human development, ushering in a new era for breastfeeding